Vojvodovo Archive Materials from the Research Carried Out by Iva Heroldová in Southern Moravia in 1973 and their Impact on Vojvodovo Research - Jakoubek, Marek (Lidé města, 2012)
The text presents an analysis of the material presented in "A Selected Edition of Archive Materials Concerning Vojvodovo from the Research Carried Out by Iva Heroldová in Southern Moravia in 1973", i.e. the materials gathered by the named researcher during her research of re-émigrés from Bulgarian Vojvodovo in newly settled villages. The analysis is aimed mainly on the meaning of the recorded testimonies of Vojvodovo contemporaries, and that on two fronts: chiefly that, which is in relation to the question of the origin of the founders of Vojvodovo in light of the so-called sectarian hypothesis, respectively, the hypothesis on the origin of the specific religiosity found in the Vojvodovo community. In the first case, we see that the origin of the first settlers of Vojvodovo was much more varied than was thought, and that Svatá Helena was not the only location that the Czechs in Vojvodovo came from. In the second case, the newly found materials show that the radical faith of the Vojvodovo Czechs was evidently not the result of past traditions, but a new element which resulted as a reaction to the influence of Protestant missionary revivals that were active in the region at the time. Aside from the mentioned issues, the analysis also discusses the question of keeping the Czech language alive among the members of the given community. In conclusion, the analysis is placed into the context of all of Iva Heroldová's work.